Pigmenting efficacy of astaxanthin fed to rainbow trout Oncorhynchus mykiss: Effect of dietary astaxanthin and lipid sources - Choubert, Georges (2010)
The aim of the present experiment was to investigate the effect of two different dietary types of oil (fish oil (FI) and olive oil (OL)) on the pigmenting efficacy of astaxanthin from the green micro-algae Haematococcus pluvialis (ALG) (total amount of carotenoid pigments 32 mg kg− 1 on a dry weight basis of which astaxanthin accounted for 98.6%) and from the synthetic astaxanthin (AST) in terms of astaxanthin serum concentration, induced muscle colour, and astaxanthin muscle retention in rainbow trout for 6 weeks. Diets with different oil sources were well accepted by fish. At the end of the experiment there were no significant differences between fish fed different diets in final mean weight, specific growth rate, or feed conversion ratio. Fish fed AST showed higher (P < 0.05) serum concentrations than those fed ALG. Moreover fish fed diets OL displayed higher (P < 0.05) serum astaxanthin levels than those fed diets FI. Fish muscle colour parameters reacted differently according to fish feed. Over 6 weeks of feeding L compared to L of initial sampling time showed a decrease more marked for trout fed ASTFI than ALGFI. Fish fed ASTOL and ALGOL displayed intermediary values. On the contrary the other colour parameters increased except hue H(°)ab which did not show any change whatever diet was fed to the fish. Chroma C*, a*, and b* data obtained for fish fed AST were higher than those obtained for fish fed ALG. Muscle astaxanthin concentrations were lower (P < 0.05) for fish fed algae than for those fed synthetic astaxanthin. After 6 weeks of experiment muscle astaxanthin levels were not different (P > 0.05) for fish fed olive or fish oil. Muscle astaxanthin retention was higher (P < 0.05) for fish fed AST than for fish fed ALG.